Answer:
9
Step-by-step explanation:
-3^3 +5*(3)^2 +3*-3
-27+5*9+(-9)
-27+45-9
=9
Answer:
-9/7
Step-by-step explanation:
Simplify and remove like terms.
The best way for him to check his answer would be to simply plug in the value found for x into the equation.
4(2) - 6 = 2
8 - 6 = 2
2 = 2
Answer:
m∠A = 31
b = 13.3
Step-by-step explanation:
Step-by-step explanation:
Pathagory and Theorem
a^2+b^2=c^2
(x-3)^2+(x-4)^2=6^2
expand:
2x^2-14x+25=36
2x^2-14x-11=0
x=(\sqrt{71}+7)/2
perimeter=(x-3)+(x-4)+6=2x-1
insert the value for x into 2x-1
+6=perimeter
Hope that helps :)